Prospects on the relationship between the communities of the Reis Catolicos neighborhood (Alcalá de Henares, Madrid) and their archaeological assets (Cadernos de Sociomuseologia, 2018)
Convergent ideas on common interest themes have led us to start some joint studies. These researches focus on archaeological management strategies in Ibero-American cities declared World Heritage by UNESCO and also the relationships between cultural heritage and communities in the most different urban contexts. This article is dedicated to one of them. It is the result of a pilot experiment carried out in the final stages of the R & D project "The Archaeological Dimension in World Heritage Cities: Advances in Heritage Management in Alcalá de Henares, Puebla and La Habana". We intended to gather data on the relationship between the communities that inhabit the peripheral quarter of Catholic Kings and the cultural assets in this context, specifically the museum ruins of the Roman city of Complutum, for behavioral guidelines for structuring a future project. The objective of this article is to present the results of the field surveys, carried out in November 2015 and June 2016, when we tried two different methodologies, namely non - systematic observation and drift. The results obtained suggest that the museum's archaeological site is part of the everyday life of neighbors, members of a changing neighborhood, currently marked by its multicultural features and resonance with other memory milestones in the neighborhood.Keywords: archaeological heritage; communities; heritage management